Experience and current issues of designing of steel and concrete composite structures of roof and floor systems (Academic journal Industrial Machine Building Civil Engineering, 2020)
The current state of the building covering structures is thoroughly investigated, in particular, the world experience in the construction and building of various roof and floor structures, made of various materials, including composites, has been studied. A thorough results analysis of theoretical studies and experimental tests on the constructive solutions effectiveness determination conducted by domestic and foreign scientists has been carried out. Based on the received information about the features of the construction and technological solutions, there were determined the advantages and disadvantages of existing construction structures, the prospective development directions. Based on the result of actual scientific and technical literature analysis, the main research objectives are formulated.
Keywords: steel and concrete composite structures; a roof; a floor; a permanent shuttering; cross-sections